Effects of systemic oxytocin and beta‐3 receptor agonist (CL 316243) treatment on body weight and adiposity in male diet‐induced obese rats - Jared D. Slattery; June R. Rambousek; Edison Tsui; Mackenzie K. Honeycutt; Matvey Goldberg; James L. Graham; Tomasz A. Wietecha; Tomasz A. Wietecha; Tami Wolden-Hanson; Amber L. Williams; Kevin D. O’Brien; Kevin D. O’Brien; et al. (Frontiers in Endocrinology)
Previous studies have implicated hindbrain oxytocin (OT) receptors in the control of food intake and brown adipose tissue (BAT) thermogenesis. We recently demonstrated that hindbrain [fourth ventricle (4V)] administration of oxytocin (OT) could be used as an adjunct to drugs that directly target beta-3 adrenergic receptors (β3-AR) to elicit weight loss in diet-induced obese (DIO) rodents. What remains unclear is whether systemic OT can be used as an adjunct with the β3-AR agonist, CL 316243, to increase BAT thermogenesis and elicit weight loss in DIO rats. We hypothesized that systemic OT and β3-AR agonist (CL 316243) treatment would produce an additive effect to reduce body weight and adiposity in DIO rats by decreasing food intake and stimulating BAT thermogenesis. To test this hypothesis, we determined the effects of systemic (subcutaneous) infusions of OT (50 nmol/day) or vehicle (VEH) when combined with daily systemic (intraperitoneal) injections of CL 316243 (0.5 mg/kg) or VEH on body weight, adiposity, food intake and brown adipose tissue temperature (TIBAT). OT and CL 316243 monotherapy decreased body weight by 8.0 ± 0.9% (P<0.05) and 8.6 ± 0.6% (P<0.05), respectively, but OT in combination with CL 316243 produced more substantial weight loss (14.9 ± 1.0%; P<0.05) compared to either treatment alone. These effects were associated with decreased adiposity, energy intake and elevated TIBAT during the treatment period. The findings from the current study suggest that the effects of systemic OT and CL 316243 to elicit weight loss are additive and appear to be driven primarily by OT-elicited changes in food intake and CL 316243-elicited increases in BAT thermogenesis.